ANALISIS CHASSIS PROTOTIPE GREEN AGV MENGGUNAKAN METODE FINITE ELEMENT ANALYSIS (FEA) DI AKADEMI KOMUNITAS TOYOTA INDONESIA - Suryawhan Arifandi; Muhammad Naufal Faqih; Harki Apriyanto (Universitas Negeri Yogyakarta, 2026)
Abstract The worsening impact of global warming is largely driven by excessive greenhouse gas carbon footprints. In 2022, Toyota reported a carbon footprint of 77,796 tons. To support environmental preservation campaigns, companies must take concrete steps to reduce emissions, one of which is through the